2018
DOI: 10.1002/adfm.201806254
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of 1D Atomic Chain Based Se Nanoplates on Monolayer ReS2 for High‐Performance Photodetectors

Abstract: Mixed-dimensional (0D, 1D, and 3D) heterostructures based on 2D layered materials have been proven as a promising candidate for future nanoelectronics and optoelectronics applications. In this work, it is demonstrated that 1D atomic chain based Se nanoplates (NPs) can be epitaxially grown on monolayer ReS 2 by a chemical transport reaction, thereby creating an interesting mixed-dimensional Se/ReS 2 heterostructure. A unique epitaxial relationship is observed with the (110) planes of the Se NPs parallel to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Mixed‐dimensional heterostructures based on ReS 2 are also attractive future applications. Qin et al demonstrated a mixed‐dimensional Se/ReS 2 heterostructure with the method of epitaxial growth. 1D van der Waals Se formed as nanoplates could be epitaxially grown on monolayer ReS 2 by a two‐step vapor deposition process.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Mixed‐dimensional heterostructures based on ReS 2 are also attractive future applications. Qin et al demonstrated a mixed‐dimensional Se/ReS 2 heterostructure with the method of epitaxial growth. 1D van der Waals Se formed as nanoplates could be epitaxially grown on monolayer ReS 2 by a two‐step vapor deposition process.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Reproduced with permission. [108] Copyright 2018, WILEY-VCH Verlag GmbH & Co. KGaA. the experimental investigation on the properties of group-VI compounds and the corresponding device applications have not yet been conducted.…”
Section: Heterostructuresmentioning
confidence: 99%
“…Qin et al reported experimental demonstration of Se/ReS 2 heterostructure. [108] The Se nanoplates are epitaxially grown on ReS 2 flakes by two-step vapor deposition. The phototransistors fabricated with Se/ReS 2 heterostructure (Figure 7f) present photoresponse from 322 to 633 nm wavelength ( Figure 7g) with fast response time less than 10 ms.…”
Section: Heterostructuresmentioning
confidence: 99%
“…For instance, the heterostructures based on topological bismuthene and superconducting materials such as NbSe 2 can be utilized to exploit the theoretically predicted Majorana fermions. Moreover, similar to WS 2 / CsPbBr 3 , the hybridization of some stable monoelemental materials with 2D materials (such as TMCs) is also a potential strategy to enhance optoelectronic performance [200][201][202]. For example, Ye et al developed the epitaxial growth of Se nanoplates on the monolayer ReS 2 , where the obtained heterostructures exhibit ultrahigh optoelectronic performance [202].…”
Section: Performance Improvementmentioning
confidence: 99%